A comparative study on the effectiveness of ordinary toothbrush and electric toothbrush (interplak) in the removal of plaque - Lopez, Judy G.
The purpose of this study was to compare the effectiveness of ordinary toothbrush and electric toothbrush in the removal of plaque among 10-11 year old children. Thirty subjects were asked to use ordinary toothbrushes on the upper and lower left quadrants. Using the O'leary plaque index, results showed that there is a significant difference in the effectiveness of the two toothbrushes. Using the Turesky plaque index, results showed that there is no significant difference in the effectiveness of the two toothbrushes. However, in both indices, the electric toothbrush was a shown to remove more plaque than the ordinary toothbrush.